Geomagnetism, Paleomagnetism and Electromagnetism Perspectives on Integrated, Coordinated, Open, Networked (ICON) Science. Issue 6 (2nd June 2022) - Ayala, C.; Beamud, E.; Huebert, J.; Jones, S. A.; Kumar, A.; Miller, S. R.; Moorkamp, M.; Pueyo, E. L.; Ruiz‐Constan, A.; Schamuells, N.; Sur, D.; Tauxe, L.; et al.
Abstract: This article is composed of three independent commentaries about the state of Integrated, Coordinated, Open, Networked (ICON) principles (Goldman et al., 2021, https://doi.org/10.1002/essoar.10508554.1 ) in the Geomagnetism, Paleomagnetism, and Electromagnetism (GPE) section and discussion on the opportunities and challenges of adopting them. Each commentary focuses on a different topic: Global collaboration, reproducibility, data sharing and infrastructure; Inclusive equitable, and accessible science: Involvement, challenges, and support of early career, BIPOC, women, LGBTQIA+, and/or disabled researchers; Community engagement, citizen science, education, and stakeholder involvement. Data sharing practices and open repository use still varies strongly between GPE communities. Some have a long tradition of data sharing; others are only starting it. Globally, GPE leadership is strongly dominated by white males and diversity may increase through the creation of Science Equality Commissions. Improved global stakeholder involvement can increase research impacts and help fight inequalities. In all investigated topics we see promising beginnings but also recognize obstacles that include a lack of funding, a lack of understanding of diversity, and prioritizing short‐term gain over long‐term benefit. Nonetheless, we are hopeful that our community will embrace ICON science. Key Points: Data accessibility is not consistent across Geomagnetism, Paleomagnetism, and Electromagnetism (GPE) disciplines. Some have a long tradition; others are still developing capabilities A global survey of GPE labs shows that leaders are predominantly white males. A network of Science Equality Commissions may increase equality Earth and planetary magnetism researchers can increase global stakeholder involvement through Coordinated, Open, and Networked investment